Sanksi Pidana terhadap Pelaku Tindak Pidana Perjudian Togel (Studi Kasus Putusan Pengadilan Negeri Bangli Nomor 23/PID.B/2020/PNBLI) - I Dewa Ayu Mira Pradewi; I Nyoman Gede Sugiartha; I Ketut Widia (Fakultas Hukum, Universitas Warmadewa, 2021)
Gambling is a bet with risk values that are intentionally aware of the risks. The formulation problem is Why togel gambling crimes are still prevalent in the community? And What is the consideration of the Judge in dropping the verdict against the perpetrators of the togel gambling crimes?. The type of research used is the normative legal research type. The approach method used a statutory approach. While technique collecting legal materials used by analyzing court decisions. In conclusion, the rising gambling in Indonesian society is due to one of the impositions of criminal sanctions against perpetrators who are too light. While the case The Verdict Number 23/PID.B/2020/PNBLI caused by economic and environmental factors involving Defendant Nyoman Pageh and is subject to a prison sentence of 5 months on charges of violating the provisions Article 303 paragraph (1) of the Criminal Code jo Article 2 of Law No. 7 of 1974. The judge's consideration verdict is based on the consideration of a juridical judge. As for the incriminating circumstances, his actions do not support the government's program in the eradication of gambling, while the circumstances that relieve is, the defendant regrets and promises not to repeat his actions again, the defendant behaved politely at the trial.